2003
DOI: 10.1002/nme.641
|View full text |Cite
|
Sign up to set email alerts
|

Level set calculations of the evolution of boundaries on a dynamically adaptive grid

Abstract: SUMMARYWe present a general algorithm for the study of the evolution of interfaces in growth processes based on the level set method, using the narrow band and the fast marching approximations, applied on a dynamically adaptive grid. A novel construction of a dynamical adaptive grid is presented. One important feature is that we establish a controllable ÿnite-width region of the highest resolution straddling the physically important boundary. This high-resolution stripe provides a better description of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…This is in contrast with many previous implementations of adaptive methods with vof or ls which restricted adaptivity to regions away from the interface (i.e. resolution along the interface was kept constant) [28,7,36,30,8,31,37,9,38,39,33,40]. A recent article by Malik et al [41] describes a two-dimensional quadtree implementation allowing variable resolution along the interface but their study is limited to the advection problem (not coupled to the momentum equation).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with many previous implementations of adaptive methods with vof or ls which restricted adaptivity to regions away from the interface (i.e. resolution along the interface was kept constant) [28,7,36,30,8,31,37,9,38,39,33,40]. A recent article by Malik et al [41] describes a two-dimensional quadtree implementation allowing variable resolution along the interface but their study is limited to the advection problem (not coupled to the momentum equation).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical methods using an implicit representation of the interface such as Volume-OfFluid (vof) [1,2,3,4] or Levelset (ls) [5,6,7,8,9,10,11,12,13] can robustly and efficiently represent evolving, topologically complex interfaces. The accurate representation of surface tension within these methods is typically more delicate than for schemes using an explicit representation of the interface [14,15,16,17] and care must be taken to avoid any imbalance between discrete surface tension and pressure gradient terms [18,19,15,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One difficulty with semi-Lagrangian methods for solving level set equations is that extreme mass loss (and thus visual artifacts) usually occurs, however [Enright et al 2004] recently showed that the particles in the particle level set method alleviate this difficulty. A quadtree structure for level set evolution was also proposed in [Sochnikov and Efrima 2003]. However, none of these authors considered level sets in the context of incompressible flows with interfaces such as water.…”
Section: Previous Workmentioning
confidence: 99%
“…Fast dynamic remeshing with octree grids makes them a natural choice for the simulation of moving interfaces and free surface flows, see, e.g., [5,6,7,8,9,10,11], octree grids became a standard tool in image processing [12].…”
Section: Introductionmentioning
confidence: 99%